Maximal power and force-velocity relationships during cycling and cranking exercises in volleyball players. Correlation with the vertical jump test - Driss, T,; Vandewalle, H.; Monod, H. (The Journal of Sports Medicine and Physical Fitness, 1998)
BACKGROUND: The aim of this study was to propose a test battery adjusted to volleyball players and to study the links between dynamic (vertical jump, force-velocity relationships and maximal anaerobic power in cranking and cycling) and static (maximal voluntary force and rate of force development in isometric conditions) performances. METHODS: The relationships between braking force (F) and peak velocity (V) have been determined for cycling and cranking exercises in 18 male volleyball players of a district league. According to previous studies, these F-V relationships were assumed to be linear and were expressed as follows: V = V0(1-F/F0), where V0 should be an estimate of the maximal velocity at zero braking force whereas F0 is assumed to be a braking force corresponding to zero velocity. Maximal anaerobic power in cycling (Pmax leg) and cranking (Pmax arm) were calculated as equal to 0.25 V0F0. The same subjects performed a vertical jump test (VJ) and a strength test on an isometric leg press with the measurement of the unilateral isometric maximal voluntary force (MVF) and indices of rate of isometric force development (RFD): maximal rate of force development (MRFD) and the time from 25% to 50% of MVF (T25-50). RESULTS: Pmax leg (15.8 +/- 1.4 W.kg-1) and V0 arm (259.6 +/- 13.1 rpm) were high but similar to the results of elite athletes, previously collected with the same protocols and the same devices. VJ was significantly with F0 leg, Pmax leg and Pmax arm related to body mass. The performances of the dynamic tests were significantly correlated and especially the parameters (V0, F0, Pmax) of the force velocity tests in cycling were significantly correlated with the same parameters in cranking. The results of the isometric tests (MVF, MRFD) were not correlated with VJ, except T25-50 of the left leg. CONCLUSIONS: A vertical jump test and a force velocity test with the arms are proposed for a test battery in volleyball players.